(untitled) (International journal of artificial intelligence, 2025)
This article delves into the intricate aspects of fostering creative thinking in preschool-aged children. It explores theoretical perspectives on creativity, delving into the crucial factors that contribute to the development of children's creative abilities. These include play activities, the cultivation of imagination, problem-solving scenarios, and the encouragement of independence. Furthermore, the article examines the impact of the social milieu, particularly the influence of family and educational settings, on the nurturing of creativity in young minds.